Systematic Literature Review: Application of Work System from Lean Maintenance and its Methodology - Azlina, Nur Azlina; Nasution, Harmein; Nurul Huda, Listiani (TALENTA Publisher, 2025)
Maintenance is an activity in maintaining and repairing a machine, with the most dominant factor being the increase in downtime. This can lead to a decrease in production output and an increase in production costs. Therefore, it is necessary to understand the maintenance repair system on the machine. Reliability-based maintenance is used to plan maintenance intervals for machines, equipment, or components that frequently experience failures. Thus, the maintenance system becomes efficient. This study aims to determine the implementation of Lean Maintenance (LM) in machine maintenance. The method used to review previous studies employs a systematic literature review. The data process was carried out by identifying, evaluating, and interpreting those related to the topic of machine maintenance. Based on the research conducted, machine maintenance using the lean maintenance (LM) approach has been proven in all reviewed scientific articles to show an efficiency increase of 60.7%, a reduction in downtime, and the ability to determine maintenance schedules. The review includes the categorization and application of the lean maintenance approach based on three parameters: technique, principle, and scope. The maintenance tools or techniques most commonly used in waste reduction are Maintenance Value Stream Mapping and Reliability-Centered Maintenance.